Repurposing the Open Global Health Library for the discovery of novel Mpro destabilizers with scope as broad-spectrum antivirals - Castillo, Francisco; Ramírez, David; Ramos, María C.; Martinez-Arribas, Blanca; Domingo-Contreras, Elisabeth; Mackenzie, Thomas A.; Peña-Varas, Carlos; Lindemann, Sven; Montero, Fernando; Annang, Fredderick; Vicente, Francisca; Genilloud, Olga; et al. (Frontiers in Pharmacology, 2024)
The emergence of new variants of concern (VoC) of coronaviruses, potentially more vaccineresistant and less sensitive to existing treatments, is evident based on the high prevalence. A prospective spread of such VoCs demands a preparedness that can be met by fast-tracking workflows aiming at viral proteins target with a clear in vitro/in vivo phenotype. Mpro (or 3CLpro) is directly involved in the viral replication cycle and in the production and function of viral polyproteins. These roles are conserved amongst betacoronaviruses like HcoV-OC43 and SARS-CoV-2, which makes the identification of new inhibitors for them a good starting point to designing broad-spectrum antivirals. We report an optimized methodology based on orthogonal cell-free assays to identify small-molecules that inhibit the binding pockets of both SARS-CoV-2-Mpro and HcoV-OC43-Mpro, which blockade correlates with antiviral activities in HCoV-OC43 cellular models. By using such fast-tracking approach against the Open Global Health Library (Merck KGaA), we have found evidence of a new antiviral activity for compound OGHL98. In silico molecular dynamics dissecting intermolecular interactions between OGHL98 and both proteases concluded that the binding mode was primary ruled by conserved H-bonds with their C-terminal amino acids and that the rational design on OGHL98 has scope against VoC proteases.